The role of childhood trauma, HPA axis reactivity and FKBP5 genotype on cognition in healthy individuals. (June 2021) - Ferrer, Alex; Soria, Virginia; Salvat-Pujol, Neus; Martorell, Lourdes; Armario, Antonio; Urretavizcaya, Mikel; Gutiérrez-Zotes, Alfonso; Monreal, José Antonio; Crespo, José Manuel; Massaneda, Clara; Vilella, Elisabet; Palao, Diego; et al.
Abstract: Cognitive impairment has been associated with both childhood adversity and abnormalities of hypothalamic-pituitary-adrenal (HPA) axis function. An interaction exists between the functional polymorphism rs1360780 in the FKBP5 gene and childhood maltreatment, influencing a variety of clinical outcomes. Our goal was to study the relationship between different types of childhood trauma, HPA axis functionality, rs1360780 genotype and cognitive function in 198 healthy individuals who participated in the study. We obtained clinical data, childhood maltreatment scores and neurocognitive performance by clinical assessment; HPA negative feedback was analysed using the dexamethasone suppression test ratio (DSTR) after administration of 0.25 mg of dexamethasone; and the FKBP5 rs1360780 polymorphism was genotyped in DNA obtained from blood samples. The results showed a significant influence of physical neglect on measures of neurocognition as well as an interaction between the DSTR and physical and emotional neglect. Regarding social cognition, a significant association was found with sexual and physical abuse as well as with rs1360780 risk-allele carrier status. Moreover, an interaction between the rs1360780 genotype and the presence of physical abuse was significantly associated with social cognition results. Our results suggest a specific impact of different kinds of childhood maltreatment on measures of neurocognition and social cognition, which might be influenced by HPA axis reactivity and genetic variants in HPA axis-related genes such as FKBP5 . Disentangling the relationship between these elements and their influence on cognitive performance might help identify susceptible individuals with higher stress vulnerability and develop preventive interventions. Highlights: We studied the relationship between childhood trauma, DSTR and FKBP5 on cognition. Neurocognition and social cognition was assessed in healthy individuals. Childhood trauma (neglect) was associated with poorer cognition. DSTR moderated the relationship between history of neglect and neurocognition. FKBP5 SNP rs1360780 moderated the relationship between physical abuse and social cognition.